OPTIMIZATION OF TREATMENT OF PATIENTS WITH DENTOALVEOLAR ANOMALIES DEPENDING ON THE CLINICAL AND FUNCTIONAL CHARACTERISTICS OF THE NASOPHARYNGEAL ZONE - Diedykova, I.V.; Shnaider, S.A.; Andrieiev, O.V.; Kibalchich, D.O. (World of Medicine and Biology, 2023)
The purpose of the study was to improve the results and reduce the treatment time for children with dentoalveolar anomalies with a constantly open mouth. The study involved 69 boys and 51 girls aged 5 to 14 years, divided into two groups (84 patients – main group; 36 patients – comparison group). Adenotomy, in all cases, preceded orthodontic treatment. 82.14 % of patients in the main group showed positive results in the form of a correct bite one year after the end of orthodontic treatment. At the same time, only 36.11 % of patients in the comparison group showed the same treatment results. It also turned out that the factor of deterioration of treatment results is a combination of several reasons on the part of the nasopharyngeal zone in a particular patient (allergic rhinitis, displacement of the nasal membrane), which complicates the course of the disease with less guaranteed correction of bite pathology (42.11 %).
Keywords: dentoalveolar abnormalities; mouth breathing; impaired nasal respiratory function; chronic nasopharyngitis; pharyngeal tonsil hypertrophy; displacement of the nasal septum; allergic rhinitis